Analytical study to find out the effect of subtrochanteric fractures on Iraqi elderly patients - Mohammed, Hasan Abdul Hadi; Ali, Raid Mubarak; Khalaf, Canaan Sattar Shuqoor (International Journal of Medical, Pharmacy and Drug Research, 2022)
Objective: This study aims to find out the effect of subtrochanteric fractures on Iraqi elderly patients Materials and methods: A cross-sectional observational study was established for patients over 75 years of age who were admitted to different hospitals in Iraq with a hip fracture in the period 2018-2020. The clinical history of each patient was reviewed, and demographic data, medical history, comorbidities, age, admission status, surgery data, and presence of complications were extracted. Results: During the study period, 100 patients were analyzed; the mean age was 83.92 ± 5.5 for the Subtrochanteric group and 82.1 ± 4.99 for the Per trochanteric group Forty-eight patients were males, with 68.5% of the population, and 22 female patients, with 31.4%. For the Subtrochanteric group, the mean length of HS was 13.22 (±6.1), and for the Pertrochanteric group, the mean length of HS was 10.1 (±2.2) with a statistically significant relationship at 0.001 p-values. Conclusion: Age, increased risk of anesthesia, need for supplemental oxygen during the postoperative period, and length of hospital stay were the main independent factors for the presence of in-hospital complications